Comparison of the HDS DBT reaction using bulk and supported catalysts - Polina P. Mukhacheva; Yuliya V. Vatutina; Ksenia A. Nadeina; Sergey V. Budukva; Maxim A. Panafidin; Vera P. Pakharukova; Mikhail V. Parfenov; Evgeny Yu. Gerasimov; Oleg V. Klimov; Aleksandr S. Noskov (Chimica Techno Acta)
The paper describes in detail the procedure for the preparation of a granular bulk NiMoW catalyst and a supported reference NiMo/Al2O3 catalyst. Mention is made of investigations of the supported and bulk catalysts by various physico-chemical methods (nitrogen adsorption-desorption method, X-ray photoelectron spectroscopy, TPD-NH3, HRTEM and X-ray diffraction analysis). The experiments to estimate catalytic activity and compare rate constant of hydrodesulfurization of dibenzothiophene using both catalysts have been carried out. It is shown that textural properties of the catalysts significantly differ. The supported catalyst has more developed specific surface area and pore volume than the bulk catalyst. TPD-NH3 showed an increased acidity of the supported catalyst in comparison the bulk catalyst. It is shown by the X-ray photoelectron spectroscopy method that in both samples Mo on the surface is present exclusively in the form of Mo4+ ion. However, the bulk catalyst differs from the supported catalyst in that it contains a larger amount of Ni as part of the active NiMo(W)S phase. The catalytic activity tests demonstrated that the bulk catalyst is more active at 240, 250 and 260°C, it is discovered that the rate constant in hydrodesulfurization of dibenzothiophene for the bulk NiMoW catalyst is twice higher at 240ºC than that of the supported NiMo/Al2O3 catalyst.